Benchmarking Single-Image Dehazing and Beyond - Li, Boyi; Ren, Wenqi; Fu, Dengpan; Tao, Dacheng; Feng, Dan; Zeng, Wenjun; Wang, Zhangyang (IEEE transactions on image processing, 2019)
We present a comprehensive study and evaluation of existing single-image dehazing algorithms, using a new large-scale benchmark consisting of both synthetic and real-world hazy images, called REalistic Single-Image DEhazing (RESIDE). RESIDE highlights diverse data sources and image contents, and is divided into five subsets, each serving different training or evaluation purposes. We further provide a rich variety of criteria for dehazing algorithm evaluation, ranging from full-reference metrics to no-reference metrics and to subjective evaluation, and the novel task-driven evaluation. Experiments on RESIDE shed light on the comparisons and limitations of the state-of-the-art dehazing algorithms, and suggest promising future directions.